TOEIC-READINESS AND TOEIC MOCK TESTS: MEASURING CIVIL AVIATION POLYTECHNIC OF SURABAYA CADETS’ PREPAREDNESS FOR TOEIC TEST - Fatmawati Fatmawati; LAILA ROCHMAWATI; Meita Maharani S (Jurnal Penelitian)
Abstract Test of English for International Communication (TOEIC) has been widely used as a reference for Indonesian aviation cadets’ English communication skills in the workplace. The present study aimed at examining cadets’ TOEIC-Readiness and TOEIC MOCK results to unravel their preparedness in doing the TOEIC test. There were 168 cadets chosen purposively based on their education grades and seven study programs at Civil Aviation Polytechnic of Surabaya. The study used a cross-sectional survey research design with a quantitative research approach. The instruments included a questionnaire of TOEIC-readiness and a TOEIC mock test Listening-Reading. The obtained data were analyzed using descriptive statistical test and paired-sample t-test. Results showed that most cadets’ final TOEIC readiness was in the very high category and the majority of their TOEIC Mock test results were in the intermediate to advanced working proficiency levels (scores: 400 - 990). The cadets’ TOEIC readiness and mock test results showed a strong positive relationship, thus, the better their readiness, the higher the TOEIC score achieved (r = .785; p = .000, N = 168). The present study implied that lecturers must know their students’ readiness before determining effective TOEIC training. Keywords: TOEIC-Readiness test, TOEIC MOCK test, Aviation cadets